2021
DOI: 10.1002/ange.202112508
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Co3d and O2p Band Centers to Inhibit Oxygen Escape for Stable 4.6 V LiCoO2 Cathodes

Abstract: High-voltage LiCoO 2 delivers ah igh capacity but sharp fading is ac ritical issue,a nd the capacity decay mechanism is also poorly understood. Herein, we clarify that the escape of surface oxygen and Li-insulator Co 3 O 4 formation are the main causes for the capacity fading of 4.6 VL iCoO 2 . We propose the inhibition of the oxygen escape for achieving stable 4.6 VL iCoO 2 by tailoring the Co3d and O2p band center and enlarging their band gap with MgF 2 doping.T his enhances the ionicity of the CoÀObond and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…Figure S22a S24 in the Supporting Information, it can be observed that the CoO bond of both LCO and LCONP with Ni TM site presented similar length at pristine state and contractive trend at highly delithiated state, implying their stronger covalency and more charge compensation from lattice O at high voltage. [6] In contrast, conspicuous divergence can be found from the model of LCONP with Ni Li site , wherein its longer CoO bond of 2.03995 Å than other samples suggested its increased ionicity between Co and O atoms. For the model of LCONP with Ni Li site at highly delithiated state, the CoO bond length became longer than its pristine state, suggesting its furtherly improved ionicity of CoO bond at high voltage.…”
Section: (8 Of 11)mentioning
confidence: 94%
See 3 more Smart Citations
“…Figure S22a S24 in the Supporting Information, it can be observed that the CoO bond of both LCO and LCONP with Ni TM site presented similar length at pristine state and contractive trend at highly delithiated state, implying their stronger covalency and more charge compensation from lattice O at high voltage. [6] In contrast, conspicuous divergence can be found from the model of LCONP with Ni Li site , wherein its longer CoO bond of 2.03995 Å than other samples suggested its increased ionicity between Co and O atoms. For the model of LCONP with Ni Li site at highly delithiated state, the CoO bond length became longer than its pristine state, suggesting its furtherly improved ionicity of CoO bond at high voltage.…”
Section: (8 Of 11)mentioning
confidence: 94%
“…FigureS24in the Supporting Information, it can be observed that the CoO bond of both LCO and LCONP with Ni TM site presented similar length at pristine state and contractive trend at highly delithiated state, implying their stronger covalency and more charge compensation from lattice O at high voltage [6]. In contrast, conspicuous divergence can be found from the model of LCONP with Ni Li site , wherein its longer CoO bond of…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Then, Co migration from Co layers to Li layers transforms the layered structure into a spinel-like/rock-salt structure. 26 2.2.2. Layer-to-spinel phase transition.…”
Section: Variation In the Bulk Phase Structure Of Licoomentioning
confidence: 99%